Transforming Manufacturing Service Quality through Enhanced Innovation Capabilities - Yunianto Agung Nugroho; Jainuri; Joni Iskandar; Dewiana Novitasari; Masduki Asbari (International Journal of Management and Economic Research (IJOMER), 2024)
This study is an empirical investigation conducted within a manufacturing industry in Tangerang. The primary objective of the research is to analyze how innovation capability and work productivity impact the service quality provided by workers to customers. Data collection was carried out using questionnaires distributed through a random sampling method to all permanent employees in the industry, resulting in 115 valid responses. The data analysis was performed using the Structural Equation Modeling (SEM) technique with SmartPLS 3.0 software. The findings indicate that both innovation capabilities and work productivity significantly and positively affect service quality. Additionally, innovation capability also has a notable positive effect on work productivity. This research proposes a model aimed at enhancing service quality in the manufacturing sector by improving workers' innovation capabilities and productivity. Ultimately, this study could help prepare both workers and companies to thrive in the context of the industrial revolution 4.0.